Lamellar precipitation of the influence of the plastic deformation In the Ni-1, 4 at. % In alloy - BENSAADA, S.; T.BOUZIANE, M. (Science des matériaux (Laboratoire LARHYSS), 2017)
The particular interest of this work is to study the influence of the plastic deformation on the mode of the precipitation reaction in Ni-1, 4 at. % In alloy. This alloy¶ is characterized by a discontinuous precipitation reaction during an ageing treatment at 600°C; a plastic predeformation does not support this reaction. The technique of analysis used in this respect is the optical microscopy, the SEM, X-ray diffraction.